3D Printing of Textiles: Potential Roadmap to Printing with Fibers. Issue 4 (1st December 2019) - Chatterjee, Kony; Ghosh, Tushar K.
Abstract: 3D printing (3DP) has transformed engineering, manufacturing, and the use of advanced materials due to its ability to produce objects from a variety of materials, ranging from soft polymers to rigid ceramics. 3DP offers the advantage of being able to print at a variety of lengths scales; from a few micrometers to many meters. 3DP has the unique ability to produce customized small lots, efficiently. Yet, one crucial industry that has not been able to adequately explore its potential is textile manufacturing. The research in 3DP of textiles has lagged behind other areas primarily due to the difficulty in obtaining some of the unique characteristics of strength, flexibility, etc., of textiles, utilizing a fundamentally different manufacturing technology. Textiles are their own class of materials due to the specific structural developments that occur during the various stages of textile manufacturing: from fiber extrusion to assembly of the fibers to fabrics. Here, the current 3DP technologies are reviewed with emphasis on soft and anisotropic structures, as well as the efforts toward 3DP of textiles. Finally, a potential pathway to 3DP of textiles, dubbed as printing with fibers to create textile structures is proposed for further exploration. Abstract : The feasibility of current 3D printing techniques for textile manufacturing is explored. Current 3D printing techniques using soft materials are examined, with a focus on printing heterogeneous/anisotropic structures. The properties required as polymers transition from fibers, to yarns, to fabrics are presented. Limitations and opportunities in 3D printing of textiles are discussed.